SYSTEMATIC REVIEW DISTRIBUSI SPASIAL VEKTOR PENYAKIT FILARIASIS DI DAERAH ENDEMIS FILARIASIS - Wulandari, Diana; Ginandjar, Praba; Yuliawati, Sri; Udijono, Ari (Jurnal Ilmiah Mahasiswa, 2020)
Mosquitoes are a vector of filariasis. Most areas in Indonesia have been declared endemic areas of filariasis. Each endemic area has a different vector and behavior. One factor that has been known to have a relationship with the distribution of mosquitoes as a vector of disease is the topography of the region which is closely related to the pattern of disease transmission. Therefore, it is necessary to have data regarding the distribution of filariasis vectors in the endemic filariasis areas. That data sources can be utilized by health policy holders as an information that is relating to the distribution of vectors for controlling filariasis. This review aims to describe the distribution of filariaisis vectors in endemic areas of filariasis in Indonesia. This research is a literature review research with a simplified approach. The research articles were collected from Google Scholar, Sciencedirect, Researhgate, and PubMed.Â The results of this review was found that species of mosquitoes caught in endemic areas of filariasis came from four genera, namely Culex, Aedes, Anopheles, and Mansonia. The density of biting mosquitoes were calculated by MHD and MBR in each study area was different because the time of catching mosquitoes was different. The high dominance of a species made the species potentially became a potential vector. The comparison of parous and nulliparous mosquitoes at the arrest at the research place showed a greater proportion of parous. The highest age of mosquitoes was Culex quinquefasciatus (28 days). Only two species of mosquitoes were confirmed as filariasis vectors namely Culex quinquefasciatus and Anopheles barbirostris. Mosquitoes that had been confirmed as vector filariasis were found spreading and gathering around the location where there were a case of filariasis.